2011
DOI: 10.1631/jzus.b1100079
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic characteristics and risk factor analysis of Demodex infestation (Acari: Demodicidae)

Abstract: Abstract:To identify sociodemographic characteristics and risk factor of Demodex infestation, 756 students aged 13-22 years in Xi'an, China were sampled for the school-based cross-sectional study. Demodex was examined using the cellophane tape method (CTP). The results showed that the total detection rate of Demodex was 67.6%. Logistic regression analysis revealed that five variables (gender, residence, sharing sanitary ware, frequency of face-wash per day, and use of facial cleanser) were found to be uncorrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
3
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 22 publications
(40 reference statements)
10
69
3
13
Order By: Relevance
“…However, it is not related as closely to Demodex infestation (OR 2.80, 95% CI, 2.34-3.36) as rosacea is (OR 7.57,95% CI,. The possible reason is that age of onset in acne vulgaris is younger than that in rosacea, which is in negative correlation with that Demodex infestation rises with age (Divani et al, 2009;Zhao et al, 2011a). On the one hand, in acne vulgaris, as adolescents gradually age, they secrete androgen, and their sebaceous glands mature, resulting in pubertal acne.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not related as closely to Demodex infestation (OR 2.80, 95% CI, 2.34-3.36) as rosacea is (OR 7.57,95% CI,. The possible reason is that age of onset in acne vulgaris is younger than that in rosacea, which is in negative correlation with that Demodex infestation rises with age (Divani et al, 2009;Zhao et al, 2011a). On the one hand, in acne vulgaris, as adolescents gradually age, they secrete androgen, and their sebaceous glands mature, resulting in pubertal acne.…”
Section: Discussionmentioning
confidence: 99%
“…Only if excess Demodex was detected could we associate the lesions with Demodex. In the present study, although we included and analyzed 63 papers about the association between Demodex infestation and acne vulgaris, only 3 English papers (Baysal et al, 1997;Zhao et al, 2011a;2011b) matched the inclusion criteria. Also only one study we could searched used SSB method (Okyay et al, 2006), and it did not match the inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth clarifying that although English papers about the association between Demodex infestation and AV are very few and mostly give negative conclusions (Baysal et al, 1997;Okyay et al, 2006), a great number of Chinese papers have reported a positive association between Demodex infestation and the development of AV (Yang et al, 2006;Ma et al, 2009;Wang et al, 2010;Zhao et al, 2011b). Moreover, effective acaricidal treatments have also supplied indirect proof of a causal relationship between Demodex infestation and AV (Yang et al, 2006;Ma et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, 140 species or subspecies have been identified, infesting the hair follicles, sebaceous glands, meibomian glands, and internal organs of 11 orders of mammals such as human, dog, sheep, cat, pig, and (Izdebska, 2010;Mederle et al, 2010), goat demodicidosis (Smith, 1961;Xu et al, 2009), livestock demodicidosis (Chakrabarti and Pradhan, 1985), and human demodicidosis (Ayres and Anderson, 1932;Ayres and Ayres, 1961;Forton and Seys, 1993;Forton et al, 2005;Zhao et al, 2010;2011a;2011c;2012c). However, the pathogenesis of demodicidosis is still uncertain, and there are no effective prevention measures.…”
Section: Introductionmentioning
confidence: 99%